An examination of the relationship between 9-12-month-old children's executive functions and social skills - YÜKSEL, MÜGE (ELSEVIER SCIENCE BV, 2015)
This study is a descriptive study aiming to identify the relationship between 9-12-month-old children's executive function performances and their social skills. Adopting a survey method, this research study used the Wisconsin Card Sorting Test and Stroop Test-TBAG Form as well as the School Social Behavioral Scale and Personal Information Form as data collection instruments. The population of the study includes 131 9-12-year-old students continuing their education in the Istanbul province. The results of the study indicate that among executive functions, 9-12-year-old children's levels of perseveration and resistance to interfering effect vary depending on their gender and their levels of perseveration, conceptualization/reasoning, and resistance to interfering effect vary depending on the grade they are in. (C) 2015 The authors Published by Elsevier Ltd.
Keywords: executive functions; social skills; neuropsychological tests; ASPERGERS-DISORDER; AUTISM; CHILDHOOD; ATTENTION; INHIBITION; BRAIN